Fasting and Refeeding Effects on Rats Stomach Tissues: Light Microscopic Study - Sönmez, Mehmet Fatih; Ozan, Enver (Fırat University, 2005)
Objectives: Fasting is a stres that causes morphological and functional disorder in gastrointestinal tract. The aim of this study was to investigate fasting and refeeding induced structural damage on rats stomach tissues. Materials and Methods: Thirty six adult Wistar male rats used in this study. Rats were divided six groups. Group I: Control, Group II: rats were fasted for seven days, Group III: refeeded rats for a days after fasting, Group IV: refeeded rats for three days after fasting, Group V: refeeded rats for five days after fasting, Group VI: refeeded rats for seven days after fasting. At the end of the experiment rats were decapitated under the cetamin anesthesia. Stomach tissues observed under light microscope after routine histological series. Results: At the stomach tissues of rats were fasted for seven days, foamy appearence and dilatation of the lumens of some gastric glads, lymphocyte and eosinophilic cell infiltration in the lamina propria and submucosa, erosion and desquamation of the surface epithelium on the apical mucosa were observed. After refeeding structural disorder on apical mucosa of the stomach, dilatation of the lumens of gastric glands and eosinophilic cell infiltration reduced by degrees. On fasted groups staining with PAS were reduced. However, refeeding exhibited similar staining to the control rats. Conclusion: It is determined that fasting leads to structural changes in the stomach mucosa. However, refeeding after fasting recovers these changes by degrees. ©2005, Fırat Üniversitesi, Tıp Fakültesi

Amaç: Açlık gastrointestinal sistemde morfolojik ve fonksiyonel bozukluklara neden olan bir stres halidir. Çalışmamızda, açlık ve açlık sonrası doyurulmanın sıçan mide dokusunda oluşturduğu yapısal değişiklikleri incelemeyi amaçladık. Gereç ve Yöntem: Çalışmada 36 adet erişkin Wistar cinsi erkek sıçanlar kullanıldı. Sıçanlar altı gruba ayrıldı. Grup I; Kontrol, Grup II; Yedi gün aç bırakılan sıçanlar, Grup III; açlıktan sonra bir gün doyurulan sıçanlar, Grup IV; açlıktan sonra üç gün doyurulan sıçanlar, Grup V; açlıktan sonra beş gün doyurulan sıçanlar, Grup VI; açlıktan sonra yedi gün doyurulan sıçanlar'dan oluşturuldu. Deney sonunda sıçanlar ketamin anestezisi altında dekapite edildi ve mide dokuları çıkarıldı. Rutin histolojik takip serilerinden geçirilerek ışık mikroskobunda incelendi. Bulgular: Işık mikroskobik incelemelerde yedi gün aç bırakılan sıçanların mide dokusunda apikal mukoza yüzey epitelinde bozulma ve dökülmeler, bazı gastrik bezlerin lümenlerinde genişlemeler ve köpüksü görünüm, lamina propria ve submukozada eozinofilik boyanan hücreler ve lenfosit hücrelerinde yoğunlaşma gözlendi. Doyurulmayla birlikte mide dokusunun apikal mukozasındaki yapısal bozukluklar giderek düzelmekteydi. Gastrik bez lümenindeki genişlemeler ve eozinofilik boyanan hücre artışı giderek azalmaktaydı. PAS ile yapılan boyamalarda açlık grubunda PAS(+)'lik azalmıştı. Yeniden doyurulma ile kontrole benzer şekilde boyanma sergilendi. Sonuç: Bu çalışmada açlığın mide mukozasında yapısal değişikliklere neden olduğu, açlık sonrası doyurulma ile bu yapısal değişikliklerin giderek düzeldiği saptandı. ©2005, Fırat Üniversitesi, Tıp Fakültesi
Açlık ve Açlık Sonrası Doyurulmanın Sıçan Mide Dokusu Üzerine Etkileri: Işık Mikroskobik Çalışma